Effect of the probiotic lactobacillus plantalum CMU-FP002 on oocyst shedding by broilers inoculated with eimeria tenella - Charunee Kasornpikul (2018)
Coccidiosis is an infectious disease that causes the most widespread health problems in the broiler industry. This study indicated that chickens fed with the probiotic Lactobacillus plantalum CMU- FP002 exhibited an 85.63% reduction in the number of oocysts of Eimeria tenella shed in the faeces compared with the control group. The average number of oocysts shed by the group fed the probiotic and a group fed an antibiotic were both significantly (P<0.05) less than the average number of oocysts shed by the control group. Coccidiosis is an infectious disease caused by a protozoan parasite of the genus Eimeria and is the most consistently reported health problem in poultry (Biggs, 1982; Rose ef al., 1987; Williams, 1999). Generally, the number of oocysts shed in the faeces is dependent on the number of sporozoites and merozoites that penetrate the enterocytes for a given inoculum dose, and so represents the infection-resistant ability of broilers. Susceptibility to Eimeria can also be assessed on the basis of the number of oocysts obtained from droppings collected for four days starting on day 6 post-inoculation (Dalloul ef al., 2005).